2007
DOI: 10.4070/kcj.2007.37.12.623
|View full text |Cite
|
Sign up to set email alerts
|

Association between the JNC 7 Classification of the Stages of Systolic Hypertension and Inflammatory Cardiovascular Risk Factors

Abstract: Background and Objectives: It is well known that the higher the blood pressure, the greater the chance of cardiovascular disease, but the factors that are responsible for this association remain largely unknown. We sought to determine whether blood pressure, in a dose-dependent way, is associated with systemic inflammation, which is a known risk factor for cardiovascular events. Subjects and Methods: We analyzed the data from 5,626 participants, aged 40-65 years, of the Third National Health and Nutrition Exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…BSY and BSG peptides also have reported antioxidant and anti-inflammatory capacities [ 7 , 15 , 16 ], which is of major importance since oxidative stress and inflammatory markers are correlated with high BP, and both pathological conditions are believed to be involved in the pathogenesis of primary hypertension [ 36 , 37 ]. In the current study these bioactivities were not explored, but if the reported antioxidant and anti-inflammatory effects are preserved after oral administration, it is expected that brewing protein hydrolysates will present multiple biological activities against the elevation of BP, having the possibility to provide more health benefits with a single bioactive component.…”
Section: Discussionmentioning
confidence: 99%
“…BSY and BSG peptides also have reported antioxidant and anti-inflammatory capacities [ 7 , 15 , 16 ], which is of major importance since oxidative stress and inflammatory markers are correlated with high BP, and both pathological conditions are believed to be involved in the pathogenesis of primary hypertension [ 36 , 37 ]. In the current study these bioactivities were not explored, but if the reported antioxidant and anti-inflammatory effects are preserved after oral administration, it is expected that brewing protein hydrolysates will present multiple biological activities against the elevation of BP, having the possibility to provide more health benefits with a single bioactive component.…”
Section: Discussionmentioning
confidence: 99%
“…The third National Health and Nutrition Examination Survey (NHANES III) analysed data from 5626 participants and revealed a higher number of circulating leukocytes in hypertensive than in normotensive participants as well as the correlation between their number and systolic BP [ 116 ]. Increased BP is also observed in patients after infusion of allo-activated T cells during cancer treatment [ 117 ].…”
Section: Clinical Evidence Linking Immune System and Hypertensionmentioning
confidence: 99%
“…[7,8] The inflammatory condition is characterized by an increased concentration of certain proteins in the blood serum, which include, among others C-reactive protein (CRP), TNF, fibrinogen, and interleukins 6 and 8. [9] Among those, TNF is one of the major cytokines of inflammatory and immunologic response, regulating the differential and growth of cells. It is primarily produced by mastocytes, macrophages as well as granulocytes, endothelial cells, fibroblasts, lymphocytes T, smooth muscle myocytes.…”
Section: Introductionmentioning
confidence: 99%